Materials of All-Ukrainian scientific-research and practical conference " Urgent issues of distance learning and telemedicine - 2012" - T, T (Zaporozhye Medical Journal, 2013)
On 17 -19 October 2012 in Zaporozhye State Medical University was held All-Ukrainian scientific-research and practical conference " Urgent issues of distance learning and telemedicine - 2012"